The Implementation of Determination of Duty on the Acquisition of Land and Building Right (BPHTB) on the Land or Building Sale and Purchase in Pekalongan City - Yodha Dhia Hogantara; Umar Ma'ruf (Jurnal Akta, 2018)
Regional taxes and regional retributions are one of the important sources of regional income to finance the implementation of regional governance. Both taxes and retribution are the source of regional income as mentioned in Law Number 28 year 2009 on Duty of the Acquisition of Land and Building Right (BPHTB). Pekalongan City has been managing Duty of the Acquisition of Land and Building Right since 2012. In the implementation of collecting tax and retribution management in Pekalongan City, it shows that there are still problems cause the target of BPHTB revenue to be hampered in the early years of the transition. This study aimed to find out and to describe the implementation of the determination of payment of duties on the acquisition of land and or building rights (BPHTB) for the sale and purchase of land and or buildings in Pekalongan City.This research used normative juridical approach. The data sources were obtained from primary and secondary data sources. The focus of this research was the implementation of the determination of the payment of duties on the acquisition of land and or building rights (BPHTB) for the sale and purchase of land and or buildings in Pekalongan City.Keywords: Taxes, Regional Taxes; Duty of the Acquisition of Land and Building Right.